(untitled) (Boston, 2005)
Benson's COMPLETE is designed for a 2-semester A&P course. In addition to the dozens of effective exercises, this lab manual is unique in that students are asked to label many of the figures to reinforce concepts. The cat is the primary dissection specimen in this manual. It is self-contained, detailed, and very logical in its approach. Because of its detailed content (textual material, line art, photos, and histology micrographs), it is generally not necessary to take the course textbook to the lab. The atlas of quality histology micrographs has always been a strong feature and makes it unnecessary to purchase an additional histology atlas.
TT. Sinh lý người và động vật
Keywords: Physiology,Anatomy,Sinh lý học,Giải phẫu học